1996
DOI: 10.1073/pnas.93.17.8962
|View full text |Cite
|
Sign up to set email alerts
|

A maize cDNA encoding a member of the retinoblastoma protein family: involvement in endoreduplication.

Abstract: Retinoblastoma (RB-1) is a tumor suppressor gene that encodes a 105-kDa nuclear phosphoprotein. To date, RB genes have been isolated only from metazoans. We have isolated a cDNA from maize endosperm whose predicted protein product (ZmRb) shows homology to the "pocket" A and B domains of the Rb protein family. We found ZmRb behaves as a pocket protein based on its ability to specifically interact with oncoproteins encoded by DNA tumor viruses (E7, T-Ag, E1A). ZmRb can interact in vitro and in vivo with the repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
146
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(153 citation statements)
references
References 33 publications
7
146
0
Order By: Relevance
“…Rb/RBR inhibitory activity can be released either as a consequence of phosphorylation or binding of specific viral proteins, such as RepA (reviewed by Gutierrez, 2000). Since Grafi et al (1996) suggested that ZmRb phosphorylation increases during the period of endoreduplication, it was hypothesized that inactivation of this protein is associated with the polyploidization process.…”
Section: Zeama;krp;1 Overexpression Can Lead To Endoreduplication In mentioning
confidence: 99%
See 2 more Smart Citations
“…Rb/RBR inhibitory activity can be released either as a consequence of phosphorylation or binding of specific viral proteins, such as RepA (reviewed by Gutierrez, 2000). Since Grafi et al (1996) suggested that ZmRb phosphorylation increases during the period of endoreduplication, it was hypothesized that inactivation of this protein is associated with the polyploidization process.…”
Section: Zeama;krp;1 Overexpression Can Lead To Endoreduplication In mentioning
confidence: 99%
“…To determine whether overexpression of Zeama;KRP;1 and Zeama;KRP;2 can cause endoreduplication in cells in which the activity of the maize RBR is reduced or eliminated, embryonic calli were transformed with gene constructs expressing the wheat dwarf virus RepA protein in the presence and absence of the maize KRPs. RepA was previously shown to interact with the maize RBR protein and stimulate the cell cycle (Grafi et al, 1996;Gordon-Kamm et al, 2002). Maize embryos were transformed by particle bombardment as described by Gordon-Kamm et al (2002), and, after culturing them on selective media, the levels of Zeama;KRPs and RepA transcripts were measured by RT-PCR and the nuclear ploidy of cells was determined by flow cytometric analysis.…”
Section: Ectopic Expression Of Zeama;krp;1 Can Induce Endoreduplicatimentioning
confidence: 99%
See 1 more Smart Citation
“…The requirement for RB in cell differentiation therefore extends beyond regulation of cell cycle entry. For example, the loss of RB function in cardioblasts affects cell differentiation by modulating the activity of cardiogenic factors (Papadimou et al, 2005).RB-related genes, termed RETINOBLASTOMA-RELATED (RBR; Ach et al, 1997), are also found in monocots (Grafi et al, 1996;Xie et al, 1996;Ach et al, 1997) and dicots (Nakagami et al, 1999;Kong et al, 2000) and even in unicellular algae (Umen and Goodenough, 2001). Animal pRb and plant RBR are similar in sequence and predicted protein structure and, thus, likely share similar functions (Flemington et al, 1993;Ramirez-Parra et al, 2003;Gruissem, 2007).…”
mentioning
confidence: 99%
“…Further, the predicted gene product encoded by this component contains an LXCXE motif (R. Wanitchakorn, G. J. Hafner, R. M. Harding & J. L. Dale, unpublished) that is associated with retinoblastoma (Rb) binding-like proteins of animal DNA tumour viruses (Picksley & Lane, 1994). A functional Rb-binding motif has been identified in the RepA early gene product of members of the subgroup I geminiviruses (Xie et al, 1995 ;Collin et al, 1996 ;Ach et al, 1997) and evidence exists for a novel plant encoded Rb-like family of regulatory proteins (Grafi et al, 1996 ;Xie et al, 1996 ;Ach et al, 1997). Based on these findings, we hypothesize that following BBTV infection, the BBTV DNA-5 gene product is the first translated and may function in creating a cellular environment permissive for viral DNA replication and transcription.…”
Section: Discussionmentioning
confidence: 99%